Cryptocurrencies: The Dawn of a New Age - Mr. Piyush Thukral (Ramanujan International Journal of Business and Research, 2018)
Cryptocurrencies have gained relevance in today's economic forum with the advent of technology and computing. Cryptocurrencies are a form of decentralized digital currency which has created a niche of investors all around the globe. The cryptographic forms of money have shown bounteous development and capital appreciation that has additionally charmed the financial specialists in the worldwide standpoint. This paper makes an endeavor to clarify what Cryptocurrencies are. It likewise tries to summon the advantages and disadvantages of the Cryptocurrencies and give some understanding into the street ahead for the Cryptocurrencies in India.